Research Trends on Students' Writing Skills: A Bibliometric Analysis Using Scopus Database - Jaja (National Research University Higher School of Economics, 2024)
Introduction: Students' writing skills positively impact their overall academic ability. Writing allows students to gain knowledge while enhancing their intelligence, initiative, courage, and willpower. Moreover, it fosters creativity, inspiring students to think outside the box. Therefore, it can be said that teaching students to write is crucial to the learning process in the classroom, even though, in reality, teaching students to write is an activity that neither teachers nor students enjoy. It seems contradictory that writing is both necessary and undesirable simultaneously. Purpose: This study investigates research trends in students' writing skills through bibliometric analysis recorded on the Scopus database from 2014 to 2023. Method: The study identified 7650 publications in the Scopus database when searching for the keyword "students, writing, and skills." Using the Prisma model, it selected 2214 publications as the sample. The data were analyzed using bibliometric analysis. Results: The analysis has revealed that Graham (f= 105), Hwang (f= 102), and Kent (f= 84) were the top three authors who investigated students' writing skills in their studies, showcasing the diversity of research in our field. Meanwhile, Reading and Writing, Asian EFL Journal, and International Journal of Instruction are the top three publishers with the most publications, further highlighting the breadth of our field. At the country level, the United States is the most productive country, with Arizona State University being the most productive university in research about students' writing. The study also found that writing in higher education contexts is the most widely researched area. Conclusion: More importantly, the bibliometrics analysis has also revealed that argumentative writing skills, collaborative writing, EFL learners, and writing attitude are some areas that need more research.